Is it too complex? The curious case of supply network complexity and focal firm innovation - Sharma, Amalesh; Pathak, Surya; Borah, Sourav B.; Adhikary, Anirban (Journal of Operations Management, 2020)
AbstractFirms have increasingly relied on their supply network for improving their innovation performance. Although the relationship between the supply network structure and innovation has been investigated, the link between supply network complexity and a firm's innovation remains unexplored. By employing transaction cost economics and the concept of a recombinatory search, we propose that the complexity dimensions (horizontal, vertical, and spatial complexity) of a supply network impact the innovation performance of a firm and that such relationships are moderated by a strategic emphasis on value creation and the influence of the firm over the supply network. With a large‐scale network data of 201 firms across six industries and 20 countries, we take a robust empirical approach that accounts for endogeneity, unobserved heterogeneity and intrafirm error correlation to test our theory. We find strong support for a nonlinear relationship (with diminishing growth) between both horizontal and vertical complexity with respect to innovation performance. We find that spatial complexity is negatively related to innovation performance. Additionally, we find that a firm's strategic emphasis and its influence indeed moderates the link between the complexity dimensions and innovation performance. Based on our findings, we offer specific managerial guidance for the effective implementation of sourcing practices.